The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00464-008-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total extraperitoneal inguinal hernia repair with nonfixation of the mesh for 1,692 hernias

Abstract: This study found TEP without mesh fixation to be safe and feasible with no increase in recurrence rates. The TEP procedure is associated with significantly less pain at 4 weeks, lower incidence of urinary retention and seroma formation, shorter hospital stay, and early resumption of normal activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 27 publications
6
47
1
Order By: Relevance
“…The duration of follow-up in the trials ranged from 8 to 36 months, which perhaps raises concerns about late recurrence. The metaanalysis showed that nonfixation of mesh in TEP would not cause increased hernia recurrence (p = 0.42); this corroborated earlier non-RCTs [20,21,[32][33][34][35] in which a total of six recurrences were reported in 3409 hernia repairs without fixation. A large RCT that compared stapled and nonstapled mesh in TAPP also confirmed this conclusion at a median follow-up of 16 months (0-263 nonstapled and 3-273 stapled; p = 0.09) [36].…”
Section: Summary Of Evidencesupporting
confidence: 85%
“…The duration of follow-up in the trials ranged from 8 to 36 months, which perhaps raises concerns about late recurrence. The metaanalysis showed that nonfixation of mesh in TEP would not cause increased hernia recurrence (p = 0.42); this corroborated earlier non-RCTs [20,21,[32][33][34][35] in which a total of six recurrences were reported in 3409 hernia repairs without fixation. A large RCT that compared stapled and nonstapled mesh in TAPP also confirmed this conclusion at a median follow-up of 16 months (0-263 nonstapled and 3-273 stapled; p = 0.09) [36].…”
Section: Summary Of Evidencesupporting
confidence: 85%
“…A randomized controlled trial of the early outcome of stapled vs unstapled techniques of laparoscopic TEP repair showed that unstapled repair scores are equivalent to their stapled counterparts with respect to recurrence and complications [27]. Absence of recurrence or chronic pain in this study is comparable to data from recent studies which suggest that mesh fixation in TEP repairs may be avoided without increasing the risk of hernia recurrence and at the same time avoiding neuropathic complications [23,28,29]. Besides, mesh non-fixation in an interesting study yielded an unaltered recurrence rate and costs $500 less [23].…”
Section: Discussionsupporting
confidence: 78%
“…[33,43]. Besides, a retrospective study on 1,692 laparoscopic TEP without fixation of the mesh showed that non fixation of the mesh is associated with a short hospital stay and early resumption of normal work [28].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis was performed for 969 patients who underwent TEP repair and were analyzed for different parameters earlier [10]. A single experienced surgical team conducted all the operations between January 2005 and December 2007 at a single large referral rural hospital.…”
Section: Methodsmentioning
confidence: 99%